Analisis Pengaruh Pendapatan Asli Daerah terhadap Ketimpangan Distribusi Pendapatan di Pulau Jawa - Resti Mutiara; Dwirani Puspa Artha (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD) on income distribution inequality in Java Island, measured using the Gini ratio. The primary focus of the research is to identify how PAD influences income inequality. Additionally, it examines the effects of the Provincial Minimum Wage (UMP), informal labor in the agricultural sector, education level measured by average years of schooling, Gross Regional Domestic Product (GRDP) growth, infrastructure measured by road length, and the Human Development Index (HDI) from 2015 to 2024. The method employed in this study is Beta Regression. The analysis results show that PAD has a negative and significant effect on income inequality. Similarly, UMP and HDI also have negative and significant effects on income inequality. Meanwhile, informal labor, average years of schooling, GRDP growth, and road infrastructure have positive and significant effects on income inequality.